A comprehensive study on FGM nanoplates embedded in an elastic medium. (15th December 2015) - Sobhy, Mohammed
Abstract: This work is devoted to investigate the bending response, free vibration, mechanical buckling and thermal buckling of functionally graded material (FGM) nanoplates embedded in an elastic medium. According to a new mixture law, the material properties of the FGM nanoplate are graded only in the thickness direction. The elastic medium is modeled as Pasternak's two-parameter elastic foundations. The four-unknown shear deformation theory incorporated in Eringen's nonlocal elasticity theory is employed to deduce the equations of motion from the Hamilton's principle. The solutions of simply supported FGM nanoplates are obtained and the results are compared with those available in the literature. Detailed numerical studies are performed to demonstrate the influences of inhomogeneity parameter, nonlocal parameter, elastic foundation stiffness, plate aspect ratio and side-to-thickness ratio on the behavior of FGM nanoplates.